EMPOWERING WOMEN THROUGH ISLAMIC MICROFINANCE: EXPERIENCE OF BMT BERINGHARJO - IZZANI ULFI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to analyze the benefits of empowering women program through Islamic microfinance program by focusing on the case of Baitulmal wat Tamwil (BMT) in Beringharjo, Indonesia. It is expected to fill the gap in the literature since most of the current studies have been focusing on conventional microfinance rather than Islamic microfinance. This study used primary data collected by interviewing participants of the Islamic microfinance program offered by the BMT. The Qualitative Content Analysis method has been used to extend the conceptual theoretical framework and give wider results description that could not be captured by the quantitative approach. The result shows that there were improvements in various socio-economic aspects of the participants such as higher income and expenditure, and more involvements in community activities, decision making and children’s education. While the focus of this study is only limited to the case of BMT Beringharjo in Jogjakarta, Indonesia, the findings from this study can be generalized and would contribute towards further improvements of future women empowerment programs throughout the globe.